Why do people believe health misinformation and who is at risk? A systematic review of individual differences in susceptibility to health misinformation - Nan, Xiaoli; Wang, Yuan; Thier, Kathryn (Social science & medicine (1982), 2022)
Health misinformation poses a significant threat to public health. Understanding why people believe health misinformation and who is at risk is crucial for developing effective interventions to reduce the harmful impact of misinformation. We conducted a systematic review of published empirical research that examined individual differences in susceptibility to health misinformation, focusing on the psychological, demographic, and behavioral correlates of health misinformation susceptibility. To guide our review on psychological correlates, we developed an integrative psychological model of susceptibility to health misinformation based on one's ability and motivation to reason. We identified 47 publications (61 empirical studies) that met our criteria. Our review suggests that subject knowledge, literacy and numeracy, analytical thinking (vs. intuitive thinking), and trust in science confer strong resistance to health misinformation, whereas conspiracy thinking, religiosity, conservative ideology, and conservative party identification are associated with more susceptibility to health misinformation. Demographically, older age and higher educational attainment predict less susceptibility to health misinformation, whereas racial minority status is associated with greater susceptibility. Behaviorally, relying on health professionals or scientists as information sources predicts less susceptibility to health misinformation, whereas social media use is associated with greater susceptibility. Susceptibility to health misinformation is driven by multiple psychological processes. Interventions for reducing the spread and impact of health misinformation should be tailored to the psychological mechanism underlying susceptibility to health misinformation. Limited resources should be used to support interventions targeted at individuals at risk. •A systematic review of individual susceptibility to health misinformation.•An integrative psychological model of susceptibility to health misinformation.•Key psychological, demographic, and behavioral correlates identified.•Implications for developing interventions to combat health misinformation.